2012
DOI: 10.1373/clinchem.2012.182717
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Late-Night Salivary Cortisol and Cortisone by LC-MS/MS to Assess Preanalytical Sample Contamination with Topical Hydrocortisone

Abstract: Hospital for providing some of the samples for this study, and Bio-Rad Laboratories for providing the Hb A 1c analyses for their methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 5 publications
1
49
0
Order By: Relevance
“…This was further investigated by Raff (30) who also found that dramatically increased salivary cortisol value by IA could be caused by cortisol contamination. In these cases, contamination with topical hydrocortisone was suggested by a normal salivary cortisone concentration as measured by LC-MS/MS and a high cortisol-to-cortisone ratio (31).…”
Section: Commonly Requested Steroidsmentioning
confidence: 99%
“…This was further investigated by Raff (30) who also found that dramatically increased salivary cortisol value by IA could be caused by cortisol contamination. In these cases, contamination with topical hydrocortisone was suggested by a normal salivary cortisone concentration as measured by LC-MS/MS and a high cortisol-to-cortisone ratio (31).…”
Section: Commonly Requested Steroidsmentioning
confidence: 99%
“…Therefore, some authors have advocated using this test as a first method of screening (33,(56)(57)(58).…”
Section: Late-night Salivary Cortisolmentioning
confidence: 99%
“…As with any method, false negatives and most especially false positives can occur in individuals with an altered sleep-wake cycle, psychiatric disorders, uncontrolled diabetes mellitus, and oral/gum disease (blood contamination) and in the elderly (27,37,55); additionally, extremely high results can be due to contamination with corticosteroids in skin creams (57). In addition, it is recommended not to smoke 24 h before collection due to glycyrrhizic acid (derived from licorice), which inhibits the 11尾-HSD2 salivary enzyme.…”
Section: Late-night Salivary Cortisolmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that over-thecounter hydrocortisone creams and ointments (containing authentic cortisol) are not widely available or used in Russia or Chile. Regardless, this is a significant issue in the United States that can be resolved by demonstrating a lack of increased salivary cortisone measured by LC-MS/MS [12].…”
mentioning
confidence: 99%